ASSESSING THE ROLE OF AI-POWERED CHATBOTS IN IMPROVING CUSTOMER EXPERIENCE IN PHARMACEUTICAL E-COMMERCE BUSINESSES IN BEIJING - Jing, Ziyi; Wongkumchai, Tachakorn; Soprakan, Chulalux; Worapongpat, Ntapat (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2024)
Purpose – The advent of new technologies like artificial intelligence in service industries has become a vital factor in creating a positive customer experience. The primary objective of organizations nowadays is developing excellent customer service that makes their customers satisfied, enhances their purchasing experience, and fosters engagement and loyalty. To achieve this, AI-enabled chatbots are widely used by businesses as they are more reliable, convenient, and accessible, provide quick resolutions as well as provide tailored recommendations for customers. This study examines the role of AI-powered chatbots in improving the customer experience in e-commerce pharmaceutical platforms in Beijing. Methodology – This study will employ a qualitative secondary research method by examining existing information on online pharmacies using AI chatbots in Beijing. Results – The findings reveal that there is huge potential for AI chatbots in online pharmacies because they can personalize customer interactions, streamline the healthcare journey of an individual, and cater to the growing demand for convenient and accessible healthcare services in an aging society like Beijing. In simple terms, healthcare treatment and diagnosis are time-consuming processes, however, with the incorporation of AI chatbots, customers gain access and convenience with personalized healthcare management, empowered self-service, 24*7 support, cost saving, eliminated hospital visits, retrieval of drug information and making them aware with proper education on medication and related services. The study indicates significant advancement in customer support and service quality within e-commerce pharmacies in Beijing. Integration of AI chat bots have shown capacities in providing personalized healthcare solutions, Real time information and also the emotional support to customers. These results together with the research objectives of assessing the impact of AI on customer satisfaction and service efficiency, as written in hypothesis 1 and hypothesis 2. Implications – The study has identified both opportunities and Threats associated with AI chatbots. Hence, the successful integration of AI chatbots in online pharmacies to improve customer experience requires proper integration between regulatory compliance, ethics, and innovation. Originality/Value – This research contributes to existing research by shredding valuable insights on the transformative potential of using AI chatbots in online business models.